2002
DOI: 10.1046/j.1365-2982.2002.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of butyrate on membrane potential, ionic currents and intracellular Ca2+ concentration in cultured rat myenteric neurones

Abstract: Myenteric neurones from 1-10-day-old rats were isolated from the small and large intestine by enzymatic digestion with collagenase. Single cells were collected and kept in culture for up to 1 week. After 1-5 days in culture, membrane potential and ionic currents were measured with the whole-cell patch-clamp technique. The intracellular Ca2+ concentration was measured with the fura-2 method. The short-chain fatty acid butyrate (50 mmol L-1) induced a reversible hyperpolarization of the myenteric neurones by abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…Therefore, these immunocytochemical data suggest that the major classes of myenteric neurons are motor and interneurons and a small population of them are AH-type sensory neurons. Similar to the present results, it has been reported that there are few AH-type neurons in cultured rat myenteric neurons by patch-clamp study (29).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, these immunocytochemical data suggest that the major classes of myenteric neurons are motor and interneurons and a small population of them are AH-type sensory neurons. Similar to the present results, it has been reported that there are few AH-type neurons in cultured rat myenteric neurons by patch-clamp study (29).…”
Section: Discussionsupporting
confidence: 82%
“…In general, the excitatory effects of SCFAs have been thought to be dependent on enteric neural reflexes that lead to activation of enteric cholinergic motor neurons (11,21,24,29,33), although direct effects on smooth muscle cells (28) and enteric neurons (2,17,18) as well as effects mediated by local release of prostaglandin have also been demonstrated (29). There is also general agreement that the SCFA-induced reflex is dependent on the presence of an intact mucosa (2,11,21,24,29,39).…”
Section: Discussionmentioning
confidence: 81%
“…enteric nervous system; neurotrophins; neuropeptides; colon; gastrointestinal motility; calcitonin gene-related peptide; brain-derived neurotrophic factor; serotonin THE SHORT-CHAIN FATTY ACIDS (SCFA), acetate, propionate, and butyrate, produced by a bacterial fermentation of dietary fiber in the colon, are an important source of energy for colonic epithelial cells (4,8,9,34). These anions regulate various colonic functions, including colonic electrolyte transport and motor activity and the growth, proliferation, and differentiation of colonic mucosal cells (4,6,7,9,18,24,35,36,39). Their concentration in the colon of most mammals, including humans, varies with the nature and availability of the substrate, the type and amount of microflora present in the colon, the pH, the rate of transit of luminal contents, and the site of measurement within the colon (1, 4, 10, 37, 38).…”
mentioning
confidence: 99%
“…The inward current at cultured rat myenteric neurones from newborn rats has been demonstrated to be mediated by a tetrodotoxin-sensitive inflow of Na + (Haschke et al 2002). Tetrodotoxin (TTX) is a neurotoxin, which inhibits voltage-dependent Na + currents in many neurones (Catterall 1980), although tetrodotoxin-resistant Na + channels are known, too (see e.g.…”
Section: Results 51mentioning
confidence: 99%
“…Changes in the intracellular Ca 2+ concentration were measured using the Ca 2+-sensitive fluorescent dye fura-2 as described previously (Haschke et al 2002). The neurones grown on coverslips were loaded for 60 min with 2.5 μmol/l fura-2 acetoxymethylester (fura-2AM) in the presence of 0.05 g/l pluronic acid.…”
Section: Calcium Imagingmentioning
confidence: 99%